Effect of Seeding Time in the Formation of Gold Nanobipyramids Toward Glucose Detection - Sukelan, Nurul Syazwani; Morsin, Marlia; Natasya Salsabiila; Nur Liyana Razali (Evolution in Electrical and Electronic Engineering, 2024)
This study explores the impact of varying seeding times on the formation of gold nanobipyramids (GNBPs) for glucose detection. The synthesis of GNBPs employs the seed-mediated growth method (SMGM), with seeding time ranging from 30 minutes to 3 hours. The investigation includes detailed UV-Vis and FESEM characterizations to study the optical and morphological properties of GNBPs. The optical characterization shows the seeding of GNBPs exhibited transverse Surface Plasmon Resonance (t-SPR) peaks around 300 to 400 nm, indicating higher presence of decahedral impurity while growth of GNBPs exhibited t-SPR peaks around 550 to 600 nm indicates the diameter of GNBPs and longitudinal Surface Plasmon Resonance (l-SPR) peaks around 850 to 950 nm linked to their aspect ratio of nanoparticles. However, the surface density of GNBPs ranged from 12.26 ± 3.729 % to 62.35 ± 12.17 %, with aspect ratios between 2.61 ± 0.067 and 3.27 ± 0.243. The optimum seeding time to synthesize GNBPs is 2 hours and proceeded into a sensing material for glucose detection through a plasmonic sensor. The plasmonic sensor is successfully developed with good stability for 600 seconds of non-stop measurement due to t-SPR and l-SPR, which exhibit consistent intensity changes over time for both bands.